WRITING RECOUNT TEXT IN THE EFL CLASSROOM: AN ANALYSIS OF STUDENTS’ COMMON DIFFICULTIES - Ayu Siska; Ridha Ilma; Deta Desvitasari (Universitas Wiralodra, 2025)
Writing serves as a fundamental medium for expressing ideas, emotions, and opinions through language. This study investigated the difficulties encountered by eighth-grade students at one of the Islamic junior high schools in Palembang in writing recount text. Employing a qualitative research approach, six students were selected through homogeneous sampling. Data were collected through interviews and analyzed using thematic analysis. The findings revealed five major areas of difficulty such as lack of ideas for content, poor abilities in organizing the structure of recount text, lack of vocabulary, lack of grammar mastery, and lack of mechanical skills. These results are intended to inform English teachers about the specific challenges students face in writing recount text, enabling them to implement more targeted instructional strategies. Additionally, the study suggests instructional strategies to address these challenges. The insights gained from this research are expected to contribute to the improvement of writing instruction in English language classrooms, especially for students at the junior high school level.